E EFEKTIFITAS MANAJEMEN PENGELOLAAN KEUANGAN KOPERASI WALISONGO DALAM MENINGKATKAN KESEJAHTERAAN SANTRI PERSPEKTIF EKONOMI SYARI’AH: THE EFFECTIVENESS OF WALISONGO COOPERATIVE FINANCIAL MANAGEMENT IN IMPROVING THE WELFARE OF STUDENTS FROM SHARI'AH ECONOMIC PERSPECTIVE - Fikria Kiki Wardani; Pratanto Rahayu, Wedi (Irtifaq, 2024)
This article discusses the effectiveness of Walisongo cooperative financial management in creating welfare for students from a sharia economic perspective. Management of the financial management of the Walisongo Islamic boarding school cooperative. The proceeds from each month's income are used to purchase goods in the cooperative and are also used for the construction of the Walisongo female Islamic boarding school. The effectiveness of financial management of the Walisongo cooperative in creating the welfare of students from a sharia economic perspective, in sharia economic principles there are planning, organizing, directing and coordinating. There, the Walisongo cooperative applies only two sharia economic principles, namely planning and coordinating, and economic principles. Sharia for organizing and directing has not been implemented in cooperatives. Keywords: Financial Management, Sharia Economic Perspective